Corporate hierarchy and goal attainability. - Shih, Michael S. H. (The Accounting Review, 1998)
The performance goal for a unit is commonly created by consolidating the goals of its subunits. This paper shows that if it is difficult (easy) for the subunits to achieve their goals, it is almost always even more difficult (easier) for the unit to whole will almost certainly not meet a goal to cut its costs by a certain percentage if the degree of cost cutting is difficult to achieve at the individual subunit levels.